A comparison of the stratified difference estimator with some monetary‐unit sampling estimators* - MENZEFRICKE, ULRICH; SMIELIAUSKAS, WALLY (Contemporary Accounting Research, 1987)
This paper extends some of the analysis reported in Duke, Leitch and Neter (1985) by comparing their “best” estimator with some new monetary unit procedures. Our finding is that some monetary unit sampling techniques compare favorably to the most efficient classical sampling techniques even when diffuse priors are used. Résumé. Cet article élargit quelques‐uns des éléments d'analyse signalés par Duke, Leitch et Neter (1985) en procédant à la comparaison de leur «meilleur» estimateur à quelques nouveaux procédés en unités monétaires. Nous constatons que quelques techniques d'échantillonnage en unités monétaires se comparent favorablement aux techniques les plus efficaces en échantillonnage classique, même lorsque des préalables diffus sont utilisés.